Perfil clínico-epidemiológico dos pacientes com micobactérias não tuberculosas isoladas em um hospital de referência do Ceará - Mota, Matheus Alves de Lima (2018)
After the development of microbiological methods, the role of these pathogens for humans being was better determined. Although innocuous for most, every year has increased the number of people with NTM infection. The goal of this study was to investigate clinical, laboratorial, epidemiological aspects and to identify risk factors associated with death of patients with NTM isolation at a reference hospital in Ceará, Northeast Brazil. It is an observational, cross-section study, with data obtained from a review of medical records for the period of January 2005 to December 2016. A total of 69 patients were described using measures of central tendency (proportions, mean and median) and dispersion (standard deviation). In the analysis, the Mann-Whitney test was used to compare means between independent variables, and Fisher's exact test to evaluate associations between categorical variables. There was a predominance of males (73.9%) and the mean age was 38.58 + 14.03 years. The majority of the patients came from the capital's metropolitan region, Fortaleza (76.5%), and 46.7% were at risk of NTM infection. The main clinical forms described were: pulmonary (60.9%) and disseminated (27.5%). The most frequently NTMs identified were M. avium (24.6%) and M. fortuitum (10.1%), and the symptoms were: cough (84.1%), fever (81.2%), weight loss (71%) and dyspnea (50.7%). Fifty-two (75.4%) patients had immunosuppression: 48 (69.6%) with HIV; three (4.4%) with Diabetes Mellitus; and one (1.5%) with neoplasia. Twenty-five (36.2%) patients were treated in a mean time of 16.75 + 15.51 months. The mortality was 24.6%, and the risk factors for deaths identified by bivariate analysis were: origin from outside the metropolitan region of Fortaleza; weight loss; HIV infection; anemia; hyperbilirubinemia; increased serum glutamic-oxaloacetic transaminase, alkaline phosphatase, lactate dehydrogenase; and impaired renal function. Among the patients with HIV, in addition to those already mentioned, the main changes related to death were: lower counts of CD4+ and CD8+ T lymphocytes; lower percentage of CD4+ T lymphocytes; and low CD4+ / CD8+ T lymphocytes ratio. Health professionals should be alert to patients with any of these conditions associated with NTM infection.